SISTEM RESERVASI ONLINE INSEMINASI BUATAN SAPI BERBASIS WEB DAN ANDROID - Mardiyono, Mardiyono; Firdasari, Isna; Pahlevi, Khumaira Anin Aliya; Sukamto, Sukamto (Departemen Teknik Elektro, Universitas Diponegoro, 2019)
The problem that is often faced in Artificial Insemination (IB) services is the slow communication of breeder and IB officers that causes delays that cause pregnant failure. Breeders contact IB officer via SMS / telephone who have not been able to provide information about cattle and the location of cowshed. While artificial insemination must be done at the right time. Another problem is IB officer is hard to find the cowshed location and it causes the delayed artificial insemination services. This research aim is to develop an online reservation system using mobile applications and technology Near Field Communication (NFC) of artificial insemination for local breeder named SIMENTAL. Cow ID detection technology are NFC and QR Code. Research method utilizes the Waterfall method which consists of analysis, design programs, coding programs, and testing systems. System testing is performed by the black box method to test all the systemâ€™s functions. SIMENTAL web application has successfully tested on three different browsers with the results of all the features that can be done well, while the SIMENTAL Android application has been implemented on 2 different Android operating systems namely Kitkat and Lollipop with the results of all the features running properly. Implementation of this system will provide convenience in contacting officers through the android application and can improve IB services by providing reports and analysis of the success rate of the IB.Â